2022
DOI: 10.1186/s13148-022-01395-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumor mutation burden involving epigenetic regulatory genes and the RhoA GTPase predicts overall survival in nodal mature T-cell lymphomas

Abstract: Nodal mature T-cell lymphomas (nMTCL) comprises a heterogeneous group of rare malignancies with aggressive biological behavior and poor prognosis. Epigenetic phenomena, including mutations in genes that control DNA methylation and histone deacetylation, in addition to inactivating mutations in the RhoA GTPase, play a central role in its pathogenesis and constitute potential new targets for therapeutic intervention. Tumor mutational burden (TMB) reflects the process of clonal evolution, predicts response to ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(41 reference statements)
1
2
0
1
Order By: Relevance
“…Although TET-2 mutations are considered secondary events in nMTCL-TFH-phenotype, different studies demonstrate an association of TET-2 and RhoA G17V mutations in these neoplasms, suggesting a biological cooperation between both mutations to promote AITL development ( 49 , 65 ). Recently, our research group demonstrated a high-rate of co-occurrence between TET-2 and RhoA mutations in Brazilian patients with non-anaplastic nMTCL, confirming the data found in previous experimental studies ( 51 , 52 ). In our population, composed of 59 patients with nMTCL, the RhoA -mut/ TET-2 -mut association was demonstrated in 42.8% of cases with nMTCL-TFH-phenotype, also being associated with a high-tumor volume represented by bulky disease ≥ 7 cm and decreased overall response rates (ORR) to primary treatment based on anthracyclines ( 51 ).…”
Section: Etiopathogenesissupporting
confidence: 91%
See 2 more Smart Citations
“…Although TET-2 mutations are considered secondary events in nMTCL-TFH-phenotype, different studies demonstrate an association of TET-2 and RhoA G17V mutations in these neoplasms, suggesting a biological cooperation between both mutations to promote AITL development ( 49 , 65 ). Recently, our research group demonstrated a high-rate of co-occurrence between TET-2 and RhoA mutations in Brazilian patients with non-anaplastic nMTCL, confirming the data found in previous experimental studies ( 51 , 52 ). In our population, composed of 59 patients with nMTCL, the RhoA -mut/ TET-2 -mut association was demonstrated in 42.8% of cases with nMTCL-TFH-phenotype, also being associated with a high-tumor volume represented by bulky disease ≥ 7 cm and decreased overall response rates (ORR) to primary treatment based on anthracyclines ( 51 ).…”
Section: Etiopathogenesissupporting
confidence: 91%
“…Mutant RhoA protein (RhoA-mut) has compromised GTP binding, which leads to alterations in the RhoA signaling pathway and impairment of its biological functions ( 24 , 50 ). The RhoA G17V mutation, associated with loss of GTPase function, is recurrently found in up to 60-70% of AITL cases, and is currently considered a diagnostic biomarker for nMTCL-TFH-phenotype ( 24 , 25 , 50 52 ). Recent studies using animal models point to a clear relationship between the RhoA G17V mutation and TFH-cell differentiation, establishing a pathogenic link between this molecular alteration and AITL development ( 49 , 53 , 54 ).…”
Section: Etiopathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Таким образом, нами был определен алгоритм расчета TMB у пациентов с ФЛ и доказана ее прогностическая значимость. В от личие от ранее опубликованных исследований [27,28], Note. Code -disease coding according to the Unified Language of Medical Systems (UMLS); n -number of genes from the studied list associated with the disease; % -the proportion of genes associated with the disease from the total number of genes from the studied list.…”
Section: рис 6 диаграмма Sankey демонстрирующая вовлеченность мутиров...unclassified